Lung cancer and tobacco smoking in Crete, Greece: reflections from a population-based cancer registry from 1992 to 2013. Issue 1 (December 2017) - Sifaki-Pistolla, D.; Lionis, C.; Georgoulias, V.; Kyriakidis, P.; Koinis, F.; Aggelaki, S.; Tzanakis, N.
Abstract Background The Cancer Registry of Crete is a regional population database that collects cancer morbidity/mortality data along with several risk factors. The current study assessed the geographical variation of lung cancer among ever and never smokers in Crete during the last 20 years. Method Lung cancer patient records (1992–2013) including information on medical history and smoking habits were obtained from the Cancer Registry of Crete. Age-Adjusted Incidence Rates (AAIR), prevalence of smoking among lung cancer patients and the Population-Attributable Fraction (PAF%) of tobacco smoking were estimated. Kaplan-Meier curves, grouped per smoking status were constructed, and spatio-temporal analyses were carried out to assess the geographical variations of lung cancer and smoking (a = 0.05). Results New lung cancer cases in Crete accounted for 9% of all cancers (AAIRboth genders = 40.2/100, 000/year, AAIRmales = 73.1/100, 000/year, AAIRfemales = 11.8/100, 000/year). Ever smokers presented significantly higher incidence compared to ex-smokers (p = 0.02) and never smokers (p < 0.001). The highest increase was observed in ever smokers (AAIR1992 = 19.2/100, 000/year, AAIR2013 = 25.4/100, 000/year, p = 0.03), while never smokers presented the lowest increase from 1992 to 2013 (AAIR1992 = 5.3/100, 000/year, AAIR2013 = 6.8/100, 000/year, p = 0.2). The PAF% of lung cancer mortality is 86% for both genders (males: 89%, females: 78%). AAIRs ranged from 25 to 50/100, 000/year, while significant geographical differences were observed among the municipalities of Crete (p = 0.02). Smokers living in the south-east urban regions presented higher risk of dying from lung cancer (RR = 2.2; 95%CI = 1.3–3.5). Conclusions The constant increase of lung cancer rates among both genders, especially in females, outlines the need for targeted, geographically-oriented, life-style preventive measures. Design of population-based screening programs, tobacco awareness campaigns and smoking cessation programs in lung cancer hot spots could be guide by these findings.